2019
DOI: 10.1007/s10560-018-0591-z
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities and Differences in Social Norms Related to Corporal Punishment Among Black, Latino and White Parents

Abstract: To establish commonalities and differences in social norms related to corporal punishment among Black, Latino, and White parents, we first examine survey data from a random sample of a nationally representative opt-in internet panel (n = 2500) to establish the frequency of corporal punishment among parents of children under five (n = 540) and their perceptions of the frequency of use of corporal punishment in their community and whether they ought to use corporal punishment. We disaggregate by race/ethnicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The American Psychological Association recently called for a ban against the use of corporal punishment for children, citing strong evidence for its deleterious effects. The issue of spanking can be challenging for many parents participating in parent education programs because this is a cultural norm in some regions of the United States and is more prevalent among some ethnic groups (Klevens et al, ). However, program content that presents evidence for the negative impact of spanking in a nonjudgmental way and encourages parents to reflect on their behavior and devise alternatives holds promise for change (Maher et al, ).…”
Section: Program Implementation and Contentmentioning
confidence: 99%
“…The American Psychological Association recently called for a ban against the use of corporal punishment for children, citing strong evidence for its deleterious effects. The issue of spanking can be challenging for many parents participating in parent education programs because this is a cultural norm in some regions of the United States and is more prevalent among some ethnic groups (Klevens et al, ). However, program content that presents evidence for the negative impact of spanking in a nonjudgmental way and encourages parents to reflect on their behavior and devise alternatives holds promise for change (Maher et al, ).…”
Section: Program Implementation and Contentmentioning
confidence: 99%
“…Additionally, many studies indicate greater use of corporal punishment in Black families than in White families (Gershoff and Grogan-Kaylor 2016). Data is conflicted regarding the use of spanking in Latino families, with some studies reporting as high as 73% of Latino families using spanking (e.g., Klevens et al 2019), and some reporting rates of spanking in Latino families to be less than that of White families (e.g., Ma and Klein 2018). Differences in the use of corporal punishment between racial and ethnic groups have been found to be associated with parental stress, parents' cognitive-emotional processing of children's misbehavior, negative perceptions of the child, beliefs regarding the effectiveness of corporal punishment, the level of importance placed on obedience, and positive attitudes regarding corporal punishment (Klevens et al 2019).…”
Section: Cultural Considerations On Spanking As a Disciplinary Practicementioning
confidence: 99%
“…These professionals should have the training to provide parents with accurate information regarding the effectiveness, or lack thereof, of spanking, potential outcomes of spanking, typical child development and the impact of spanking, and alternative appropriate disciplinary techniques. Positive alternatives to corporal punishment can include strategies to reinforce (and increase) the desired behavior, such as clarifying expectations and consequences beforehand and praising for good behavior; and strategies to reduce the undesired behavior such as redirection, removal of dangerous objects, ignoring the behavior, reasoning, taking away privileges, and time-outs to address the undesirable behaviors (Klevens et al 2019).…”
Section: Build Knowledge and Awarenessmentioning
confidence: 99%
“…Using a nationally representative opt-in internet panel, Klevens et al (2019) explored social norms associated with the use of corporal punishment among Black, Latino, and White parents. Drawing on quantitative survey data as well as qualitative focus group data, the authors document the frequency of self-reported and perceived spanking among the sample.…”
mentioning
confidence: 99%
“…Vaughan-Eden, Holden, and LeBlanc (2019) provide a general commentary on the topic of corporal punishment, drawing on the key themes outlined by Klevens et al (2019) and Fleckman et al (2019). In their commentary, the authors describe the historical landscape of initiatives to reduce and ban corporal punishment, including a current national movement to end the hitting of children.…”
mentioning
confidence: 99%